Benefits or costs? The effects of diversification with cross-industry knowledge on corporate value under crisis situation - Li, Zhi; Wei, Jiuchang; Marinova, Dora; Tian, Jingjing (Emerald, 2020)
Purpose: This paper aims to explore the explanations of “information effect” and “agency effect” of corporate diversification with cross-industry knowledge under a crisis situation.